Exact solution for stresses/displacements in a multilayered hollow cylinder under thermo-mechanical loading - Yeo, W.H.; Purbolaksono, J.; Aliabadi, M.H.; Ramesh, Singh; Liew, H.L. (Elsevier, 2017)
In this study, a new analytical solution by the recursive method for evaluating stresses/displacements in multilayered hollow cylinder under thermo-mechanical loading was developed. The results for temperature distribution, displacements and stresses obtained by using the proposed solution were shown to be in good agreement with the FEM results. The proposed analytical solution was also found to produce more accurate results than those by the analytical solution reported in literature.